Effect of perioperative β blockade in patients with diabetes undergoing major non-cardiac surgery: randomised placebo controlled, blinded multicentre trial. Issue 7556 (22nd June 2006) - Juul, Anne Benedicte; Wetterslev, J⊘rn; Gluud, Christian; Kofoed-Enevoldsen, Allan; Jensen, Gorm; Callesen, Torben; N⊘rgaard, Peter; Fruergaard, Kim; Bestle, Morten; Vedelsdal, Rune; Miran, André; Jacobsen, Jon; et al.
Abstract: Objectives To evaluate the long term effects of perioperative β blockade on mortality and cardiac morbidity in patients with diabetes undergoing major non-cardiac surgery. Design Randomised placebo controlled and blinded multicentre trial. Analyses were by intention to treat. Setting University anaesthesia and surgical centres and one coordinating centre. Participants 921 patients aged > 39 scheduled for major non-cardiac surgery. Interventions 100 mg metoprolol controlled and extended release or placebo administered from the day before surgery to a maximum of eight perioperative days. Main outcome measures The composite primary outcome measure was time to all cause mortality, acute myocardial infarction, unstable angina, or congestive heart failure. Secondary outcome measures were time to all cause mortality, cardiac mortality, and non-fatal cardiac morbidity. Results Mean duration of intervention was 4.6 days in the metoprolol group and 4.9 days in the placebo group. Metoprolol significantly reduced the mean heart rate by 11% (95% confidence interval 9% to 13%) and mean blood pressure by 3% (1% to 5%). The primary outcome occurred in 99 of 462 patients in the metoprolol group (21%) and 93 of 459 patients in the placebo group (20%) (hazard ratio 1.06, 0.80 to 1.41) during a median follow-up of 18 months (range 6-30). All cause mortality was 16% (74/462) in the metoprolol group and 16% (72/459) in the placebo group (1.03, 0.74 to 1.42). The difference in risk for the proportion of patients with serious adverse events was 2.4% (− 0.8% to 5.6%). Conclusions Perioperative metoprolol did not significantly affect mortality and cardiac morbidity in these patients with diabetes. Confidence intervals, however, were wide, and the issue needs reassessment. Trial registration Current Controlled Trials ISRCTN58485613 [controlled-trials.com .